COPING STRATEGIES IN STUDENTS WITH PHYSICAL - Anastasia A. Kiseleva (Вестник Кемеровского государственного университета, 2017)
The current research revealed that students with physical conditions (health limitations) in general seldom take responsibility for the events happening to them, and rarely analyze the situation and their possibilities and more often try to distance from the problem. According to the data obtained, the handicapped students demonstrate problems with coping strategies in the cognitive sphere. The article also gives an analysis of the gender peculiarities of coping behavior among students with physical conditions. It has been revealed that female students with health limitations are more often ready to have a conflict or to try to cope with the problem by subjectively diminishing its importance and degree of their emotional involving into it, as compared to their so-called conditionally healthy peers. However, male students with health limitations are less ready for confrontation, rarely accept responsibility for the problem and its solution; they also have less tendency for direct analysis of the situation and possible variants of behavior, as well as working out the strategy for the problem solving and planning their actions considering objective conditions, previous experience and resources. Also, the article analyzes the character of relations between different coping strategies of the students with physical conditions those conditionally healthy. It has been revealed that the main relations between different copings of conditionally healthy students are represented by the scales «Problem-solving Planning» and «Positive reestimation». It is possible to suggest that for these (healthy) students these coping strategies compose the core of the mechanisms of coping behavior. On the contrary, the students with health limitations do not demonstrate any definite correlation connections. Thus, it is impossible to speak about a definite core in the system of coping behavior in students with physical conditions.